Effect of Tuff Powder Mineral Admixture on the Macro-Performance and Micropore Structure of Cement-Based Materials - Shi, Yan; Li, Xiang; Li, Yang; Peng, Ziling; Li, Jiazheng (Frontiers in Materials, 2020)
The effects of the tuff powder which is produced from southwestern China on cement mortars fluidity, compressive strength (Rc) and dry shrinkage are investigated in this paper. In addition, the pore structure, hydration products and morphology of the blend cementitious materials are studied by means of MIP, XRD and SEM, respectively. On this basis, the fractal dimension of pore surface area (Ds) is also proposed in this paper. The results show that with the increasing mixing amount of tuff powder, Rc presents a gradual decreasing trend while fluidity and dry shrinkage increase first and then decrease. Meanwhile, the total porosity and the proportion of harmful pores (>100 nm) present a gradual increasing trend. By contrast, the proportion of the little harmful (20–100 nm) and harmless pores (below 20 nm) shows a decreasing trend. As the curing age increases, the pore diameter becomes smaller, the distribution of the most probable pore size is mainly between 5 and 50 nm at 180 days. The pozzolanic activity of tuff powder is low, and the consumption of Ca(OH)2 through the secondary hydration reaction is very limited. The pore surface area of the paste exhibits obvious fractal characteristics. With the increase of curing age and the decrease of tuff powder mixing amount, the Ds becomes larger because the hydration process gradually increases the density of the paste. However, the addition of tuff powder increases the proportion of the macropores and reduces the strength of the paste. For engineering applications, the recommended amount of tuff powder in concrete should be less than 20% to obtain the optimal comprehensive performance, such as mechanical properties, durability properties and pore structure.